А System for Input of 3D Objects into Computing Environment (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper proposes an approach for design and implementation of automated 3D scanner used for input of mechanical 3D objects into computing environment. The presented model of 3D scanner is based on kinematic diagram of positioning system with 5 degree of freedom – 3 linear and 2 rotational, each driven by servo motors. For distance measuring is used laser scanning head with rotational triangulation. The paper describes also algorithms for functional control of the scanning process, obtaining of point cloud, object reconstruction and export to standard CAD format. Keywords